To what extent financial development is important in promoting economic growth in OECD countries. - Blanco-Arana, María del Carmen (My University, 2018)
This paper revisits the relationship between economic growth and the main determinants of financial development in The Organisation for Economic Co-operation and Development (OECD) countries during the period 1990-2016. Using a random effects model, we provide empirical evidence of different aspects of financial development in order to show which of these characteristics of financial development help to explain economic growth in OEDC countries in terms of finances through a panel data model for the period examined. We pay special attention to the main determinants of the financial system and verify their influence on economic growth even when we control for other key country-level factors relating to economic growth. Results show that an increase in domestic credit provided by financial-sector, in market capitalization and in the turnover ratio of domestic shares entails a significant positive effect on the Gross Domestic Product (GDP) per capita. Among other socioeconomic determinants related to economic growth, expenditure in education, the inflation and unemployment rates appear highly significant in the economic growth of the analysed countries.
Keywords: Desarrollo económico y social; Finanzas; Financial development; Economic growth; Panel data; Random effects model